Stem Radial Growth Is Negatively Related to Tree Defoliation and Damage in Conifers, Northern Italy - Ferretti, Marco; Ghosh, Sucharita; Gottardini, Elena (Frontiers in Forests and Global Change, 2021)
Although several manipulative experiments provided evidence for a negative effect of defoliation on tree growth, results from observational studies were less univocal. This may be due to the ability of observed defoliation to reflect the health status of individual trees, to the influence of site condition and to the amplitude of time window used for growth assessment. Here, we investigated the relationship between two tree health indicators (crown defoliation, damage symptoms) and annual (measured by tree-ring width on 69 Norway spruce trees) and periodical (5-year and 10-year diameter increments, 346 trees from five coniferous species) tree growth. Data originated from 14 (seven for tree rings) ICP Forests Level I plots in Trentino, northern Italy. Diameter, defoliation and damage were measured between 1997 and 2011 as part of the annual crown condition survey, while cores for tree-rings were collected on a sub-sample of trees in 2012. We carried out regression modeling combined with model selection in one-step (periodical data) and two-step (annual data) approaches, using moving averages for the annual data with varying time window widths. Our results indicated an overall negative correlation between defoliation and annual or periodical stem diameter growth. The relationship between defoliation and growth changes in relation to the time window considered, and becomes stronger when data are aggregated over longer time windows (>3 years), when also the occurrence of damage symptoms plays a significant role. The effect of the amplitude of the time windows for data aggregation is probably due to the mechanisms behind the defoliation-growth relationship, which may change according to the causal factors involved. In particular, when larger time windows are considered, short-term fluctuations are likely to be smoothed out, and more general patterns may emerge. We concluded that radial growth is significantly negatively related to defoliation, and this supports the use of defoliation as a rapid indicator for forest health and vitality.